2022
DOI: 10.3389/fped.2022.961268
|View full text |Cite
|
Sign up to set email alerts
|

The etiology and clinical features of non-CAH primary adrenal insufficiency in children

Abstract: BackgroundThe most common cause of primary adrenal insufficiency (PAI) in children is congenital adrenal hyperplasia; however, other genetic causes occur. There is limited epidemiological and clinical information regarding non-CAH PAI.MethodsData for patients diagnosed from January 2015 to December 2021 at a tertiary hospital in northern China were retrospectively analyzed. We excluded those with CAH, which is the most common pathogenic disease among PAI patients. Next-generation sequencing was used for geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(36 reference statements)
0
2
0
Order By: Relevance
“… 52 A retrospective, single-center study (Northern China, between 2015 and 2021) on 16 pediatric patients with non-CAH AD showed through a next-generation sequencing analysis that 87.5% of them had a gene mutation, ABCD1 being the most frequent (37.5%) followed by NR0B1 (25.0%), NR5A1 (12.5%), and 6.25% for each AAAS , and NNT . 53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 52 A retrospective, single-center study (Northern China, between 2015 and 2021) on 16 pediatric patients with non-CAH AD showed through a next-generation sequencing analysis that 87.5% of them had a gene mutation, ABCD1 being the most frequent (37.5%) followed by NR0B1 (25.0%), NR5A1 (12.5%), and 6.25% for each AAAS , and NNT . 53 …”
Section: Resultsmentioning
confidence: 99%
“…52 A retrospective, single-center study (Northern China, between 2015 and 2021) on 16 pediatric patients with non-CAH AD showed through a next-generation sequencing analysis that 87.5% of them had a gene mutation, ABCD1 being the most frequent (37.5%) followed by NR0B1 (25.0%), NR5A1 (12.5%), and 6.25% for each AAAS, and NNT. 53 An interesting analysis on reported cases included 55 patients with sphingosine-1-phosphate lyase insufficiency syndrome (SPLIS) harboring SGPL1 mutations; 71.2% of patients had AD and 32.7% had hypothyroidism with kidney disorders affecting 80% of them; among 30 SGPL1 mutations, the most frequent was c.665G > A (p.Arg222Gln) in onefifth of cases. 67 According to Ron et al, since 2017 when SGPL1 mutations were first identified, 36 cases were reported…”
Section: Gene Testingmentioning
confidence: 99%
“…3,4 Pulmonary thrombosis (PT) is the most frequent thrombotic complication of MPP in children, 4,5 and domestic literature reports that Mycoplasma pneumoniae (MP) infection is one of the main risk factors for PT in this population. 6 Without timely diagnosis and treatment, PT ranks as the third leading cause of MPP-related mortality. 7 Currently, there is a paucity of literature on risk factors for PT in patients with MPP.…”
mentioning
confidence: 99%